2019
DOI: 10.1038/s41377-019-0225-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal metasurface with space–time phase modulation

Abstract: Creating materials with time-variant properties is critical for breaking reciprocity that imposes fundamental limitations on wave propagation. However, it is challenging to realize efficient and ultrafast temporal modulation in a photonic system. Here, leveraging both spatial and temporal phase manipulation offered by an ultrathin nonlinear metasurface, we experimentally demonstrated nonreciprocal light reflection at wavelengths around 860 nm. The metasurface, with travelling-wave modulation upon nonlinear Ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 44 publications
0
121
0
1
Order By: Relevance
“…One of the most interesting and promising applications of space-time metastructures is the possibility to break Lorentz reciprocity without the need of magnetic or nonlinear materials. Theoretical [41][42][43] and experimental [44][45][46] studies have shown the possibility to attain nonreciprocal reflection or transmission effects via a metasurface imparting a suitable space-time phase gradient. In a recent study [30], this concept was implemented and demonstrated by relying on a space-time coding digital metasurface.…”
Section: Nonreciprocal Reflection Effectsmentioning
confidence: 99%
“…One of the most interesting and promising applications of space-time metastructures is the possibility to break Lorentz reciprocity without the need of magnetic or nonlinear materials. Theoretical [41][42][43] and experimental [44][45][46] studies have shown the possibility to attain nonreciprocal reflection or transmission effects via a metasurface imparting a suitable space-time phase gradient. In a recent study [30], this concept was implemented and demonstrated by relying on a space-time coding digital metasurface.…”
Section: Nonreciprocal Reflection Effectsmentioning
confidence: 99%
“…Despite these achievements, the basic principles for realizing optical nonreciprocity remain limited as a result of the time-reversal symmetry and linear nature of Maxwell’s equations. The existing approaches can be grouped into three categories with the following requirements 1 3 : (i) magnetic-field-induced breaking of time-reversal symmetry 26 29 , (ii) spatiotemporal modulation of system permittivity 30 36 , and (iii) nonlinearity 37 , 38 . However, these principles either encounter difficulties in integration 39 , require stringent experimental conditions 40 , or have limited performance 38 .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of new ideas, including time‐modulated meta‐atoms, [ 5 ] temporal multilayers, [ 6–11 ] space–time‐periodic diffraction gratings, [ 12 ] Fresnel drag, [ 13 ] and time‐dependent epsilon‐near‐zero media, [ 14 ] just to mention a few, have been proposed and explored, also revisiting old results in the field of electrical engineering [ 15–17 ] and taking inspiration from emerging concepts in classical and quantum physics such as “time‐crystals.” [ 18,19 ] Arguably, one of the most promising application scenarios for space–time metastructures involves breaking Lorentz reciprocity without the need of magnetic bias, and several candidate strategies have been explored theoretically [ 20–24 ] and experimentally. [ 25–29 ]…”
Section: Introductionmentioning
confidence: 99%